The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.6061/clinics/2012(04)07
|View full text |Cite
|
Sign up to set email alerts
|

Psychological crisis intervention for the family members of patients in a vegetative state

Abstract: OBJECTIVES:Family members of patients in a vegetative state have relatively high rates of anxiety and distress. It is important to recognize the problems faced by this population and apply psychological interventions to help them. This exploratory study describes the psychological stress experienced by family members of patients in a vegetative state. We discuss the effectiveness of a psychological crisis intervention directed at this population and offer suggestions for future clinical work.METHODS:A total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
0
14
0
3
Order By: Relevance
“…A brief, group psychological session for relatives of patients in a vegetative state was associated with a decrease in psychological symptoms such as somatization, obsessive–compulsive behaviour, depression, and anxiety compared to the control group who did not receive the intervention (Li & Xu ). The brief single‐session group intervention was in the format of a critical incident stress debriefing, which included participants describing what happened and their first thoughts concerning the event, discussing their emotional reactions, and receiving training to increase coping abilities (Li & Xu ). In another RCT, a teachable brief intervention for persons who attempted suicide was associated with greater patient satisfaction, improvement in motivation to address their problems, and significant improvements on reasons for living compared to the group who received usual care (O'Connor et al ).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…A brief, group psychological session for relatives of patients in a vegetative state was associated with a decrease in psychological symptoms such as somatization, obsessive–compulsive behaviour, depression, and anxiety compared to the control group who did not receive the intervention (Li & Xu ). The brief single‐session group intervention was in the format of a critical incident stress debriefing, which included participants describing what happened and their first thoughts concerning the event, discussing their emotional reactions, and receiving training to increase coping abilities (Li & Xu ). In another RCT, a teachable brief intervention for persons who attempted suicide was associated with greater patient satisfaction, improvement in motivation to address their problems, and significant improvements on reasons for living compared to the group who received usual care (O'Connor et al ).…”
Section: Resultsmentioning
confidence: 96%
“…The studies examined outcomes of patient satisfaction, readiness to change problematic behaviours, reasons for living and suicidal ideation, psychological symptoms, social role functioning, and interpersonal relationships. Components of brief intervention varied throughout the studies; however, brief crisis interventions that considered trauma‐informed principles had positive outcomes (Li & Xu ; O'Connor et al ), as opposed to brief crisis interventions that did not consider trauma‐informed principles (Van Oenen et al ). A brief, group psychological session for relatives of patients in a vegetative state was associated with a decrease in psychological symptoms such as somatization, obsessive–compulsive behaviour, depression, and anxiety compared to the control group who did not receive the intervention (Li & Xu ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, another study in China showed that the psychological interventions reduces anxiety and enhance coping power of PVS caregivers (33). We believe the caregivers of PVS patients should be visited periodically by clinicians, and underwent some psychological and physical supports in the hospitals.…”
Section: Discussionmentioning
confidence: 97%